Reductive mammaplasty with superior-based pedicled dermo-glandular flap: our experience - Valeriani, M; Mezzana, Paolo; Terracina, Madonna F. S (Acta chirurgiae plasticae (English ed.), 2001)
The authors used a reductive mammaplasty technique with superior pedicled dermoglandular flap described by Lalardrie in 1972 and modified by Lauro. Twenty-eight patients who presented medium to heavy macromasty were treated. In all these cases the aesthetic result was vety satisfactory and major complications, like extended tissue necrosis, were not encountered. This method proves safe and effective in cases of significant gigantomasty for the following reason: for the efficient vascularization of the flap, it is possible to carry out significant transposition of the areola-nipple complex without risk of complications. This technique can be used in less serious cases in conjunction with other equally easy techniques. Because of its simplicity, this technique also allows younger, less experienced, surgeons to approach this type of surgery with the necessary peace of mind.
Keywords: mamoplastika; Humans; lidé; Gigantism; prsy; ženské pohlaví; Mammaplasty; gigantismus; Female; Breast